The Impact of the Financial Education of Executives on the Financial Practices of Medium and Large Enterprises - CUSTÓDIO, CLÁUDIA; MENDES, DIOGO; METZGER, DANIEL (Journal of Finance, 2025)
ABSTRACT We study the impact of an MBA‐style executive education course in finance on corporate policies and firm performance targeting top managers of medium and large Mozambican enterprises. Using a randomized controlled trial, we find that the educational treatment induces changes in financial policies that improve firm performance. Specifically, a reduction in working capital (0.4 to 0.5 standard deviations) increases cash flow, and in turn long‐term investments. This effect operates primarily through a reduction in accounts receivable (0.4 to 1 standard deviations). Our findings show that targeted educational interventions can build managerial capital and enhance corporate performance by improving financial decision making among executives.